HUBUNGAN LINGKAR LENGAN ATAS IBU HAMIL TERHADAP ANTROPOMETRI BAYI BARU LAHIR DI RUMAH SAKIT IBU DAN ANAK ANANDA KOTA MAKASSAR - Rizka Amalia; Azizah Nurdin; Jelita Inayah Sari; Andi Irhamnia Sakinah (JURNAL KEDOKTERAN, 2020)
The newborn’s body dimensions are influenced by maternal nutritional status that can be determined by measuring mid upper arm circumference (MUAC). The aim of this study was to determine relationship between maternal MUAC and anthropometry of newborn at Ananda Women and Children Hospital Makassar. The method used in this study was analytic with cross sectional design. A total of 200 pregnant women underwent delivery at Ananda Women and Children Hospital Makassar were taken by purposive sampling method. The study data were sourced from primary data i.e. demographic data, maternal MUAC and newborn anthropometry which included weight, length, head circumference, and chest circumference that were measured immediately after birth. Data were analyzed using the Chi-Square test on the IBM SPSS 23. The results of this study showed a significant relationship between maternal MUAC with body length (p = 0,000), head circumference (p = 0,000), and chest circumference (p = 0,013) of newborns, but no significant relationship was found between maternal MUAC with body weight of newborns (p = 0.127). This study conclude that maternal MUAC influence the anthropometry of newborns on the parameters of body length, head circumference, and chest circumference.